Medical Costs of Patients Undergoing Esophageal Atresia Repair are Mainly Influenced by Associated Malformations - Pardey, Nicolas; Zeidler, Jan; Blaser, Jochen; Becker, Nastassja; Dingemann, Jens; Ure, Benno; Schukfeh, Nagoud (European Journal of Pediatric Surgery, 2024)
Background Esophageal atresia (EA) is a rare disease requiring surgical repair, usually within the first days of life. Patients with EA require intensive postoperative care and often have comorbidities. There is a lack of data on the costs incurred by patients with EA during the first year of life.Methods Anonymized claims data were provided by the Techniker Krankenkasse (∼10.8 million clients). Data were extracted for patients who had an inpatient diagnosis of EA (International Classification of Diseases [ICD]: Q39.0 or Q39.1) and a reconstruction of the esophageal passage in case of atresia (Operationen-und Prozedurenschlüssel [German version of ICPM, International Classification of Procedures in Medicine; OPS] 5–428.0 to 5–428.7, 5–316.1 or 5–431.0) during their first hospital stay. All patients were in their first year of life at initial hospitalization (2016–2020) and were followed up for 1 year. Costs, length of hospital stay, and duration of mechanical ventilation and differentiated OPS services were analyzed using descriptive statistics. Multiple linear regression was used to analyze the determinants of hospital costs.Results A total of 119 patients with EA were included (55.5% male). The mean cost of the 1-year observation period was €89,736 ± 97,419 (range €12,755–640,154). The increasing costs of the initial hospitalization led to a disproportionate increase in the costs of the 1-year observation period. The presence of an associated malformation combined with surgical complications was associated with almost five-fold higher costs than in patients without an associated malformation and an uncomplicated course (€193,103 ± 157,507 vs. €39,846 ± 33,473). The mean duration of mechanical ventilation was 23.2 ± 43.1 days and the mean length of hospital stay was 80.3 ± 77.2 days.Conclusion To our knowledge, this is the first study to investigate the costs of EA patients in the first year of life. The presence of an associated malformation combined with surgical complications was associated with almost five-fold higher costs than in patients without an associated malformation and an uncomplicated course.
Keywords: esophageal atresia; economic; pediatric; congenital malformations; surgical complications